Presenting a Causal Model of Suicidal Behavior Based on Early Childhood Trauma the Mediation of Thwarted Belongingness in Suicide Attempters in Tehran - Mahboubi Matboo, Mojgan; Ahmadi, Vahid; Soleimannejad, Homeira; Jafari Mehdiabad, Amirhossein (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: According to reports, a suicide attempt is made every 40 seconds in the world, some of which have serious consequences for the attempter. The present study investigated the relationship between suicidal behavior in suicide attempters and early childhood trauma, with the mediation of thwarted belongingness. Materials and Methods: The current study is descriptive and correlational. A total of 365 patients who attempted suicide and were hospitalized at Baharloo Hospital in Tehran in 2022 were selected through convenience sampling. The Childhood Trauma Questionnaire (CTQ), Interpersonal Needs Questionnaire (INQ) for thwarted belongingness, and the Suicidal Behaviors Questionnaire-Revised (SBQ-R) were administered to the suicide attempters. The Sobel test was used to examine the mediation hypotheses, and structural equation modeling (SEM) was employed to evaluate the proposed model. Findings: The results showed that there are positive and significant relationships between Childhood trauma score and suicidal behavior (r=0.42, p<0.001), and thwarted belongingness and suicidal behavior (r=0.395, p<0.001). The model fit indices confirmed the path from Childhood trauma to suicidal behavior and the path from Childhood trauma with the mediation of thwarted belongingness. Conclusion: The results of this study showed that Childhood trauma plays a crucial role in suicidal behavior, both directly and indirectly through the mediation of thwarted belongingness. Therefore, teaching families and schools to prevent childhood traumas, as well as providing treatment for individuals with childhood traumas and addressing their interpersonal needs (thwarted belongingness), can effectively prevent and reduce suicidal behavior.